2001
DOI: 10.1080/00039890109604049
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Formaldehyde on Peak Expiratory Flow and Irritant Symptoms

Abstract: The authors studied the respiratory effects of formaldehyde exposure among students who dissected cadavers in a gross anatomy laboratory. Peak expiratory flow and respiratory symptoms were measured before and after each weekly laboratory session. Each of 38 students was exposed to formaldehyde for 2.5 hr/wk for 14 wk. Individual, daily formaldehyde measurements averaged 1.1 ppm (standard deviation = 0.56 ppm). Multivariate models demonstrated two different time scales of effect of formaldehyde on peak expirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…In allergic people, there is a risk of development of allergic sensitization to inhalant allergens, and symptoms commonly occur [29]. This may explain the more severe reaction of allergenic students in the form of nose and respiratory system related symptoms after FA inhalation, the main route of its exposure [30]. However, it is still unclear whether sensitization and FA-related symptoms are induced by formaldehyde-specific IgE [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…In allergic people, there is a risk of development of allergic sensitization to inhalant allergens, and symptoms commonly occur [29]. This may explain the more severe reaction of allergenic students in the form of nose and respiratory system related symptoms after FA inhalation, the main route of its exposure [30]. However, it is still unclear whether sensitization and FA-related symptoms are induced by formaldehyde-specific IgE [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, however, was not supported by the results of a longitudinal study including college students who dissected cadavers in anatomical laboratories. The formaldehyde potency of eye irritation (in addition to nose and throat irritation) diminished during a period of 14 weeks of 2.5 hours of exposure weekly (184). Furthermore, the nasal irritation threshold for nicotine is the same for smokers and nonsmokers, and this similarity indicates that repeated exposure to nicotine does not lower the irritation threshold (185).…”
Section: Gaseous Pollutantsmentioning
confidence: 96%
“…FEV 1 ) were normal on the Monday morning before exposure to formaldehyde, but reduced significantly after a day of work and exposure to formaldehyde, suggesting bronchoconstriction 4) . Kriebel et al (2001) in a study on anatomy laboratory students also found that exposure to 1.1ppm of formaldehyde for 2.5 h/wk reduced peak expiratory flow (PEF) by 1% per ppm 5) . Similar results have been reported by Erdem et al in smoking formaldehyde exposed individuals 6) .…”
Section: Introductionmentioning
confidence: 98%